2010
DOI: 10.1590/s0103-50532010000200010
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of experimental parameters in the determination of zinc in sea water by adsorptive stripping voltammetry

Abstract: Otimizamos um procedimento para a detreminação de zinco em água do mar usando voltametria de redissolução de onda quadrada (SWAdsV) com 8-hidroxiquinolina (oxina) como adsorvente e agente complexante. Inicialmente um estudo univariante da corrente máxima do complexo Zn-Ox em função do pH foi feito para obter os valores adequados de corrente. Posteriormente as condições experimentais foram selecionadas usando um planejamento multivariado experimental. Variaveis como pH, concentração de oxina (C ox ), tempo (t a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
0
6
0
2
Order By: Relevance
“…The contributions of stripping voltammetry combined with the use of microelectrodes for quantification of metals in water samples were revised by Xie et al 7 Examples of using of stripping voltammetry for quantification of heavy metals include: determination of Cu 2+ in ethanol fuel, 8,9 Pb 2+ in ethanol fuel, 8,10 gasoline 11 and fruit juice, 12 As 3+ in natural water, 13 cadmium in natural 14 and sea water, 15 zinc in sea water, 16 etc.…”
Section: Introductionmentioning
confidence: 99%
“…The contributions of stripping voltammetry combined with the use of microelectrodes for quantification of metals in water samples were revised by Xie et al 7 Examples of using of stripping voltammetry for quantification of heavy metals include: determination of Cu 2+ in ethanol fuel, 8,9 Pb 2+ in ethanol fuel, 8,10 gasoline 11 and fruit juice, 12 As 3+ in natural water, 13 cadmium in natural 14 and sea water, 15 zinc in sea water, 16 etc.…”
Section: Introductionmentioning
confidence: 99%
“…Already Arancibia et al (2010) used the factorial design in two stages, in order to optimize a procedure for determining zinc in seawater using voltammetric square wave stripping voltammetry (SWAdsV). In both cases, we used the planning on two levels, with four factors at first, being the variables analyzedpH, concentration of oxine (Cox), time (TADs) and potential (Eads) and the second adsorption optimum values of pH and Cox, by variance analysis showed that these two are the most significant parameters mentioned.…”
Section: Fig3: Use Of Factorial Design In Scientific Papersmentioning
confidence: 99%
“…A determinação de íons metálicos em solos, águas e em organismos vivos expostos a contaminação é frequente. [31][32][33][34] Repula et al estudaram a presença de Cr e Pb em briófitas e pteridófitas coletadas em um córrego que recebe descarte de curtume. O HMDE e técnica de pulso diferencial foram utilizados para as determinações dos íons metálicos.…”
Section: Determinação De íOns Metálicos Usando O Hmdeunclassified
“…A preocupação com este compartimento ambiental é significativa, devido aos possíveis riscos aos quais organismos aquáticos estão expostos. 33,34,[37][38][39][40][41][42][43] No mesmo sentido, alguns trabalhos também avaliaram a presença de metais em águas de torneira e água envasada. [44][45][46][47][48][49] Arab and Alshikh avaliaram a presença de Cd, Cu, Fe, Pb Zn, Se em amostras de águas de torneira de diferentes pontos da cidade de Jeddah na Arábia Saudita, durante um ano empregando voltametria de redissolução por pulso diferencial e HMDE como eletrodo de trabalho.…”
Section: Determinação De íOns Metálicos Usando O Hmdeunclassified